Bioimpedance body measures and serum lipid levels in masculine depression - Zimmermann, Claudia von; Brückner, Lena; Mühle, Christiane; Weinland, Christian; Kornhuber, Johannes; Lenz, Bernd (Frontiers in psychiatry, 2022)
BackgroundMajor depressive disorder (MDD) is a main reason for suicide, and serum lipids are involved in both affective disorders and related suicidal behavior. Moreover, masculine depression has been suggested as a subtype of depression with an increased risk for suicide. Here, we studied the relationship between body measures, serum lipids, suicidal thoughts, and masculine depression.MethodsDepressed patients (44% women) were divided by a sex-separated median-split into a group of 81 “patients with masculine depression” (mean age ± standard error: 36.4 ± 1.6 years) and a group of 82 “patients with non-masculine depression” (age 45.7 ± 1.6 years) according to the Male Depression Risk Scale. We compared body measures, serum lipid levels, and past suicidal ideation between these groups and explored differences between these groups and 176 healthy controls (51% women; age 37.2 ± 1.0 years).ResultsPatients with masculine depression did not significantly differ from patients with non-masculine depression in any of the body measures, lipid markers, or suicidal thoughts. Compared to healthy controls, both patient groups showed significantly higher body fat (B[masculine depression] = 0.041 and B[non-masculine depression] = 0.050), lower high-density lipoprotein (HDL) cholesterol (B = -0.045 and -0.044), and a higher risk for suicidal thoughts (B = 3.927 and 2.663) than healthy controls. Suicidal thoughts were significantly associated with lower low-density lipoprotein (LDL)/HDL ratios (B = -0.455) in patients with depression and with higher LDL cholesterol levels (B = 0.020) in healthy controls subjects.LimitationCorrelational study design and focus on in-patients.ConclusionIn the studied cohort, masculine depression was not significantly associated with the analyzed parameters of body measures, serum lipids, or suicidal thoughts in in-patients with depression.
Gesehen am 19.12.2023